1985
DOI: 10.1016/0306-4530(85)90037-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of endogenous ACTH levels to visual-attentional functioning in patients with congenital adrenal hyperplasia

Abstract: The within subject experimental approach of either doubling cortisone medication dose or withdrawing steroid treatment for 36 hr preceding behavioral testing was found to induce corresponding significantly elevated or suppressed plasma ACTH levels, as measured by radioimmunoassay, in six of eight adults diagnosed as having congenital adrenal hyperplasia (CAH). During the session characterized by elevated ACTH levels, the CAH patients exhibited significantly reduced median reaction times on the Sternberg Item R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Improvements of memory functions, in this task, are reflected by supe rior RTs for the larger set sizes, only. Recently, Veith et al [1985] confirmed these promising results in patients with congenital adrenal hyperplasia. Sternberg reaction performance, in this experiment, improved in a consis tent manner across all four target set sizes when ACTH secretion was enhanced by prior withdrawal of steroid replacement medication.…”
Section: Learning and Memorysupporting
confidence: 71%
See 1 more Smart Citation
“…Improvements of memory functions, in this task, are reflected by supe rior RTs for the larger set sizes, only. Recently, Veith et al [1985] confirmed these promising results in patients with congenital adrenal hyperplasia. Sternberg reaction performance, in this experiment, improved in a consis tent manner across all four target set sizes when ACTH secretion was enhanced by prior withdrawal of steroid replacement medication.…”
Section: Learning and Memorysupporting
confidence: 71%
“…Accord ingly, ACTH peptides did not affect delayed recall per formance in several other studies Schneider et al. 1981;Veith et al. 1985].…”
Section: Learning and Memorymentioning
confidence: 98%
“…The melanocortins are involved in skin physiology, behaviour, learning and memory [54], [55], [56]. ACHT, or peptides derived from it, are implicated in attention, visual attention, analytical thinking, spatial awareness and musical ability [57], [58], [59], [60]. MC5R is a single exon gene less than 1 kb in length.…”
Section: Discussionmentioning
confidence: 99%
“…Visual attention and the associated motor responses have also been found to improve when with pubertal delay were found to increase self-reported aggressive behaviour in boys and girls, respectively [59]. ACTH levels were raised [52]. In MPHD patients, the observed subnormal perceptual-motor skills were attri-Moderate concentrations of oestradiol have been associated with positive effects on mood and behaviour, whereas buted to ACTH deficiency on the basis of the inverse correlation between hydrocortisone replacement dose and a lack of oestradiol is tied to depression and emotional lability.…”
Section: Irradiation Effects In Adultsmentioning
confidence: 93%